Upaya Mereduksi Academic Burnout Melalui Layanan Konseling Kelompok dengan Teknik Reframing Pada Siswa SMA Kelas XI MA Pertanian Kota Madiun - Evaelistarosa Yula Selinda; Noviyanti Kartika Dewi; Silvia Yula Wardani (Universitas Mathla'ul Anwar Banten, 2026)
Academic burnout is a psychological condition experienced by students who feel emotionally, physically, and mentally exhausted due to continuous academic demands. This condition may reduce students’ learning motivation, concentration, academic confidence, and involvement in classroom activities. The present study aimed to examine the change in students’ academic burnout after receiving group counseling services using the reframing technique. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The research subjects were five eleventh-grade students of MA Pertanian Kota Madiun who were identified as having a high level of academic burnout. The subjects were selected through purposive sampling based on initial observation, interviews with the school counselor, and academic burnout scale scores. The instrument used in this study was an academic burnout scale consisting of 25 Likert-type items. The data were analyzed using the Wilcoxon Signed Rank Test. The results showed a decrease in students’ academic burnout scores after the intervention. The mean pretest score was 77, while the mean posttest score decreased to 51.2. The Wilcoxon test showed an Asymp. Sig. (2-tailed) value of 0.043, indicating a significant difference between pretest and posttest scores. These findings suggest that group counseling with the reframing technique has the potential to reduce students’ academic burnout by helping them develop more adaptive perspectives toward academic demands. However, the results should be interpreted carefully due to the limited number of subjects and the absence of a control group.